THE INFLUENCE OF LEADERSHIP, WORK TRAINING AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. TITAN WIJAYA, NORTH BENGKULU - Adji Mucharom Adji; Islamuddin (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
This study aims to determine the influence of leadership, job training, and the work environment at PT. Titan Wijaya, North Bengkulu. This is a descriptive quantitative study. The subjects of this study were employees of PT. Titan Wijaya, North Bengkulu, located on Jl. Kota Bani, North Bengkulu, Bengkulu. The sampling method employed was non-probability, specifically accidental sampling. The number of respondents in this study was 40. Data analysis techniques included multiple linear regression analysis and hypothesis testing using the t-test and F-test. The results of this study indicate that Leadership has a positive effect on Employee Performance, Job Training has a positive effect on Employee Performance, Work Environment has a positive effect on Employee Performance, and Leadership, Job Training, and Work Environment together have a significant effect on Employee Performance at PT. Titan Wijaya, North Beng